2009
DOI: 10.1093/occmed/kqn165
|View full text |Cite
|
Sign up to set email alerts
|

Audit of quality of diagnostic procedures for occupational asthma

Abstract: Although the diagnostic procedures were mostly of sufficient quality, the performance of serial measurements of PEF at the workplace and the time to diagnosis should be substantially improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…47 Comparisons of surveys and surveillance have shown that routine screening of exposed workers through occupational health underestimates the frequency of disease. 19 …”
Section: Delayed Diagnosismentioning
confidence: 99%
“…47 Comparisons of surveys and surveillance have shown that routine screening of exposed workers through occupational health underestimates the frequency of disease. 19 …”
Section: Delayed Diagnosismentioning
confidence: 99%
“…Although many consensus practice guidelines on diagnostic procedures have been issued and made widely available over the years-the latest addition being the British Thoracic Society initiative [48••]-they are still insufficiently applied, as shown by audits in Finland [49]. Serial assessment of peak expiratory flows comparing periods at work and away from work has been advocated since 1980 because this approach is superior to two single cross-shift assessments of spirometry (as was recently reconfirmed) [50].…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…[9][10][11][12] Studies from a range of countries, however, have identified average delays of several years in the patient journey for symptomatic workers, which in part relate to the condition being under-recognised in primary care. [13][14][15][16] National published guidelines for the prevention, The full version of this paper, with online Appendix, is available at www.thepcrj.org …”
Section: Introductionmentioning
confidence: 99%
“…PRIMARY CARE RESPIRATORY JOURNAL www.thepcrj.org [13][14][15][16] which may in part relate to deficiencies in undergraduate and postgraduate occupational training. This is highly relevant for affected workers, since early and accurate diagnosis linked with exposure modification offers the best prognosis, both for health and socioeconomic outcomes.…”
mentioning
confidence: 99%